Peran Program Pelatihan Terhadap Kinerja Karyawan Pada PT. Telkom Akses Makassar - Yusi Irensi Seppa (Academic Bright Collaboration, 2024)
One of the important investments for a company is human resources, which is the key to the company's success in surviving and developing well because employees are seen as an important asset in the company. To achieve the company's goals so that it can survive and develop well, it requires a good training program and suitable for employees. The training activities held are effective in improving human resources, because the quality of knowledge and abilities of employees increases so that they can also improve the quality of work and be competitive. Training activities starting from the training preparation stage and then implementing good training can support the success of the entire training program carried out. This research aims to find out the role of training programs on performance at PT. Telkom Access Panakkukang Makassar so that by realizing good employee performance, one of which is through training, it can increase company profits. This research uses a descriptive qualitative approach to determine employee performance through the implementation of training by describing the phenomena and facts that exist or occur in the research object. Data was obtained from observations and interviews. The research was conducted at PT. Telkom Access Panakkukang Makassar. The data sources used are primary data sources and secondary data sources. The data collection technique used was observation by conducting thorough observations and freelance interviews. Based on the research results, it can be concluded that the training program in terms of preparation and implementation of training at PT Telkom Access Makassar has been able to carry out its role well because its role is very important in improving the quality of work. Training activities are effective in improving human resources, because they increase employee knowledge and abilities.